2003
DOI: 10.1007/s10327-003-0044-0
|View full text |Cite
|
Sign up to set email alerts
|

PCR primers for identification of opine types of Agrobacterium tumefaciens in Japan

Abstract: The polymerase chain reaction (PCR) is a rapid, precise method for detecting and identifying pathogenic bacteria. In addition to the published primers for identification of Agrobacterium tumefaciens up to species level, two sets of primers were designed to identify the nopaline and octopine types of Agrobacterium tumefaciens. The RBF-RBR primer set designed based on the nopaline type T-DNA right border detected the nopaline type A208 and R225f strains, and the ocsF-ocsR primer set derived from the ocs gene of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 10 publications
(13 reference statements)
0
6
0
1
Order By: Relevance
“…tumefaciens infection. Although the diagnosis was completed using the biosensor developed in this study, we isolated the causative bacterium from the root gall tissues to perform a PCR test using the bacterial DNA and the RBF (5′-TGACAGGATATATTGGCGGGTAA-3′) and RBR (5′-TGCTCCGTCGTCAGGCTTTCCGA-3′) primer set designed based on the nopaline type T-DNA right border 14 . The A .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…tumefaciens infection. Although the diagnosis was completed using the biosensor developed in this study, we isolated the causative bacterium from the root gall tissues to perform a PCR test using the bacterial DNA and the RBF (5′-TGACAGGATATATTGGCGGGTAA-3′) and RBR (5′-TGCTCCGTCGTCAGGCTTTCCGA-3′) primer set designed based on the nopaline type T-DNA right border 14 . The A .…”
Section: Resultsmentioning
confidence: 99%
“…tumefaciens detection and diagnosis. Methods to diagnose crown galls with PCR have been developed in various ways 1214 . Rhizobium and Agrobacterium are very similar in many respects, and it is difficult to distinguish these genera using PCR-based assays.…”
Section: Introductionmentioning
confidence: 99%
“…(1) Agrocinopine PCR conditions consisted of one cycle of 94°C for 4 min, 34 cycles of 94°C for 1 min, 58°C for 1 min, and 72°C for 1 min, and finally one cycle of 72°C for 5 min. (2) RBF-RBR (nopaline right border forward and reverse) primers; 2 min denaturation at 94°C, followed by 35 cycles at 94°C, 60°C, and 72°C for 1 min at each temperature [36]. (3) ocsF-ocsR (octopine genes forward and reverse) primers; 3 min denaturation at 94°C, followed by 35 cycles of 94°C, 58°C, and 72°C for 1 min at each temperature.…”
Section: Methodsmentioning
confidence: 99%
“…(3) ocsF-ocsR (octopine genes forward and reverse) primers; 3 min denaturation at 94°C, followed by 35 cycles of 94°C, 58°C, and 72°C for 1 min at each temperature. The final elongation was at 72 for 5 min [36]. PCR products were analyzed by electrophoresis on 1% agarose gels and stained with ethidium bromide to detect PCR-amplified DNA fragments.…”
Section: Methodsmentioning
confidence: 99%
“…2). Suzaki et al, 2004) ;2) Ti プラスミド特異的プライマー (Cubero et al, 2006Haas et al, 1995;Picard et al, 1992;Pionnat et al, 1995;Pulawska and Sobiczewski, 2005;Puopolo et al, 2007;Sobiczewski et al, 2005) ;3)Ri プラスミド特異的プライマー (伊予住・市川,1999) ;4)特定の系統(オパイン型など) の病原性プラスミドのみを対象としたプライマー(Bini et al, 2008Dong et al, 1992;Eastwell et al, 1995;Kaufmann et al, 1996;Szegedi and Bottka, 2002;Tan et al, 2003;Weller and Stead, 2002;Yakabe et al, (Table 2) to determine which pathogenic plasmid respective strains carry and which pathogenic state they belong to. Amplification of the DNA fragments (780-784 bp) from the 16S rRNA gene (16S rDNA) (internal control) of the respective strains indicated that the respective PCR reactions were completed properly.…”
Section: Te Buffer 340unclassified